Aerodynamic force and moment measurement for crosswind stability assessment in a compact wind tunnel - Akitoshi MATSUI (The Japan Society of Mechanical Engineers, 2017)
Rolling stock is sensitive to crosswind because of its large side area, so crosswind stability must be assessed when rolling stock is developed. In the European Union, aerodynamic force and moment under crosswind need to be measured in a wind tunnel experiment in accordance with European Norm EN14067-6, which describes the methods of crosswind stability assessment. In this report, we present a measurement system developed on the basis of the European Norm to check the aerodynamic force and moment of the designed rolling stock in a compact wind tunnel. For precise measurement, by effectively using a limited air flow rate, an adequate quality of flow must be acquired from the nozzle and the same flow around the train model must be simulated as the European wind tunnels, in which the measured aerodynamic force and moment were described as the reference value in the European Norm. To achieve this flow, a wide nozzle and a splitter plate were developed. For the wide nozzle design, first, from the relationship between the train model scale and the specifications, the train model scale and the outlet size of the wide nozzle were determined, and an adequate contraction from the inlet area to the outlet area was designed. The splitter plate height was optimized in a simulation to satisfy the boundary layer thickness and acquire sufficient vertical space above the train model. The results revealed that the developed measurement system can satisfy the equipment requirements and flow specifications defined in the European Norm. Additionally, the rolling moment around the leeward rail of a wind tunnel benchmark vehicle model, which is defined in European Norm, was measured within a mean tolerance 0.086 from the reference value described in the European Norm. This shows that the developed measurement system for a compact wind tunnel has the same measurement accuracy as the reference wind tunnel described in the European Norm.